Analysis Of Consumer Behavior Towards The Adoption Of Digital Platform Use At PT Bank Sulutgo - Nilam Basuki; Raden Roro Ratna Roostika (UNIVED Press, 2025)
The development of digital technology requires the banking industry to continuously innovate in providing optimal services to customers. PT Bank SulutGo has implemented various digital platforms to enhance banking transaction efficiency and convenience. This study aims to analyze the adoption level, user satisfaction, and challenges in using PT Bank SulutGo’s digital platform. A qualitative research method was employed, utilizing interviews, observations, and documentation during an internship at PT Bank SulutGo. The findings indicate that digital platform adoption is still influenced by customer preferences for conventional banking services. Key factors determining user satisfaction include ease of use, transaction security, and the perceived benefits of digital services. However, some challenges, such as feature limitations, technical issues, and data security concerns, hinder optimal platform usage.